2013
DOI: 10.1002/em.21782
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity induced by Taenia solium and its reduction by immunization with calreticulin in a hamster model of taeniosis

Abstract: Genotoxicity induced by neurocysticercosis has been demonstrated in vitro and in vivo in humans. The adult stage of Taenia solium lodges in the small intestine and is the main risk factor to acquire neurocysticercosis, nevertheless its carcinogenic potential has not been evaluated. In this study, we determined the genotoxic effect of T. solium infection in the hamster model of taeniosis. In addition, we assessed the effect of oral immunization with recombinant T. solium calreticulin (rTsCRT) plus cholera toxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Consistent with these findings, a positive correlation between MN frequency and relative expression of these cytokines, as well as disease activity index was observed. Accordingly, we have previously reported the reduction of genotoxic damage by rTsCRT in an experimental model of taeniosis [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with these findings, a positive correlation between MN frequency and relative expression of these cytokines, as well as disease activity index was observed. Accordingly, we have previously reported the reduction of genotoxic damage by rTsCRT in an experimental model of taeniosis [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Calreticulin is a multifunctional protein involved in diverse cellular and immunological processes and is a component of the E/S products of several helminths [ 18 20 ]. We have previously described the ability of orally administered recombinant Taenia solium calreticulin (rTsCRT) as a candidate vaccine to reduce worm burden in a hamster model of taeniosis by inducing a IL-4 and hyperplasia of goblet cells in the small intestine and to reduce the DNA damage brought about by the presence of the tapeworms [ 21 , 22 ]. rTsCRT was also able to induce production of IL-4 and IL-10 when incubated in vitro with mesenteric lymph node and spleen cells [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Asia, there is a similar scenario to Latin America, where most of the cases of cysticercosis are original from the region, except in some countries like Japan and Oman where patients with cysticercosis, in contrast, have a history of traveling to endemic regions [48]. However, intensive work, research and improvement of socioeconomic conditions have demonstrated reduction of taeniasis and NCC, as has been reported in Mexico [57,21,41,4345]. …”
Section: Discussionmentioning
confidence: 96%
“…Taeniasis is produced by both agents after accidental cysticerci ingestion in undercooked contaminated meat and minimal gastrointestinal clinical manifestations may occur. Moreover, when Taenia solium eggs are ingested, a systemic invasion occurs in several tissues called cysticercosis causing serious complications mostly in the central nervous system and invading also muscles, eyes, and subcutaneous tissue [57]. Exposure, given such conditions would be important in endemic areas, not just for people living there, but also for travelers and visitors, especially in touristic zones [3,610].…”
Section: Introductionmentioning
confidence: 99%
“…The parasitic flatworms are also known to cause genotoxicity in humans and animals (Salazar et al 2013). The biological agents including parasites contributed to 16.1 % of total cancer cases diagnosed and 2 million new cancer cases were attributed to infections.…”
Section: Introductionmentioning
confidence: 99%